The best beloved thing is justice : the life of Dorothy Wright Nelson - Kloppenberg, Lisa A. (New York, NY : Oxford University Press, 2022)
Dorothy Wright Nelson was a prominent federal judge on the level just below the U.S. Supreme Court for over 40 years. Although women had few opportunities in law when she graduated, she became one of the first female law professors and deans. The book offers an in-depth look at her life and her rise as a national expert in what is now the major field of alternative dispute resolution or conflict resolution. Featuring extensive interviews with judges, professors, and legal leaders, they offer first-hand accounts and multiple perspectives on how she was an extraordinary trailblazer in a traditional, male-dominated profession.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 9, 2022).
Keywords: Nelson, Dorothy Wright, -- 1928-; Judges -- United States -- Biography; Law teachers -- United States -- Biography; Women judges -- United States -- Biography; Mediation -- United States; Justice, Administration of -- United States